Pemanfaatan Sistem Informasi Geografis dalam Pembuatan Peta Dasar Skala 1 : 5.000 dengan Menggunakan Citra Resolusi Sangat Tinggi PLEIADES (Studi Kasus Kota Padang Panjang) (Universitas Negeri Semarang, 2022)
This study discusses how to orthorectify Pleiades 1A images of Padang Panjang City with the image-to-image method on aerial photos using an unmanned aerial vehicle (UAV), and how to make a base map from these results. The base map was generated through an interpretation process at a scale of 1:5,000 with a spatial resolution of 0.5 m. The process of extracting map information is done through digitizing map elements such as buildings, waters, transportation networks, toponyms, and land cover. The digitization process is carried out using a geographic information system (GIS) application and the digitized data is stored in a geodatabase. The results of the image orthorectification process obtained the root mean square error (RMSE) values of 0,906 respectively and accuracy horizontal 1,375 m. The results of the digitization process are 42 maps with a scale of 1:5,000 with map sheet numbers ranging from 0715-6211A to 0715-62112B containing 27 land cover elements